2019
DOI: 10.1111/tbed.13323
|View full text |Cite
|
Sign up to set email alerts
|

Co‐circulation and characterization of novel African arboviruses (genus Ephemerovirus ) in cattle, Mayotte island, Indian Ocean, 2017

Abstract: SummaryMayotte is an island located in the Mozambique Channel, between Mozambique and Madagascar, in the South Western Indian Ocean region. A severe syndrome of unknown aetiology has been observed seasonally since 2009 in cattle (locally named “cattle flu”), associated with anorexia, nasal discharge, hyperthermia and lameness. We sampled blood from a panel of those severely affected animals at the onset of disease signs and analysed these samples by next‐generation sequencing. We first identified the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…So, we suspect co-existence and cocirculation of some unknown virus (as the case in Mayotte; Dacheux et al, 2019), which is dominating over the progress of passages.…”
Section: Re Sults and Discussionmentioning
confidence: 98%
“…So, we suspect co-existence and cocirculation of some unknown virus (as the case in Mayotte; Dacheux et al, 2019), which is dominating over the progress of passages.…”
Section: Re Sults and Discussionmentioning
confidence: 98%
“…Thirdly, although mortalities due to bovine ephemeral fever are relatively uncommon, the most severe cases usually occur in older, larger cattle; in this case the diseased animal was a mature, 2.5 year-old bull. Fourthly, although co-circulation of BEFV and other ephemeroviruses has been reported previously [13], no isolations of BEFV were made during this period from other cattle located at the farm, suggesting BEFV infections were not occurring in the herd at the time. Serological evidence also indicated that BEFV had already passed through the herd several months previously.…”
Section: Discussionmentioning
confidence: 61%
“…BEFV occurs as a single serotype throughout its geographic range through tropical and sub-tropical regions from South Africa to Japan [3]. Although eight other antigenically related, but distinct, ephemeroviruses had been described prior to this study, none have ever been isolated from animals showing signs of disease or shown to cause ephemeral fever experimentally in cattle, with the notable exception of a single recorded outbreak of KOTV in Nigeria [11,12] and tentatively the as yet uncharacterised Mavingoni virus in Mayotte Island [13]. Indeed, several of these other ephemeroviruses, such as KIMV and ARV, commonly infect cattle in Australia and elsewhere, with no evidence of association with disease [14,16].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The virus was widely distributed through Africa, the Middle East, Asia, and Australia. Phylogenetic analysis based on the surface glycoprotein (G) gene demonstrated that BEFV isolates are grouped into four lineages with different geographical origins: Africa, the Middle East, Asia, and Australia (9,10). Recently, several BEFV isolates clustered into Asian lineage have been appeared in Turkey and Iran, indicating its expansion to the westward (11,12).…”
Section: History Of Endemic and Emerging Arboviruses Affecting Domestmentioning
confidence: 99%